FOTOGRAFI UNTUK MEDIA MASSA - Prasetyo, Andry (Capture : Jurnal Seni Media Rekam, 2010)
The benefits of photography as a tool for an effective and reliable communicating, are summarized in Photo journalistic . In one side, photography has the feel of reality in detail the reliable, furthermore, photography is also a more rapidly digested, knew and understood. So the response and reaction will be given to the information that there will be more quickly and precisely. Moreover with the invention of digital technology will shorten the process of delivering information to better results and faster. Through a combination of drawings and manuscripts, photographs contained in a newspaper or magazine will give us information as is appropriate. Because the image is recorded based on trust-owned, which is something that is absolutely necessar y to inform the sustainability of human life on this earth. In addition, not only, the works of photo-journalistic produced have the factual, reality and detail that is strong, but also contains the values of the beauty of high, given the work that was created by a photojournalist eye will be seen by millions of human beings throughout the world through the mass media both print and electronically.Keywords: Photography, Mass Media, Script.